The use of Digital Game-Based Learning (DGBL) in teachers’ training: a scoping review - Ragni, Benedetta; Toto, Giusi Antonia; di Furia, Marco; Lavanga, Andreana; Limone, Pierpaolo (Frontiers in Education, 2023)
Taking care of teachers’ competencies is essential to determine a satisfactory level of quality in teaching, with a crucial impact on the proper functioning of educational services. In order to be effective, this training must consider the most recent developments in the field of technology-enhanced learning, such as Digital Game-Based Learning (DGBL). Although research in the educational field has shown that DGBL enhances learning processes, promoting learning by doing and cooperative learning as well, with all its positive effects, there is still a paucity of studies on the subject; hence, the intrinsic reason for the present investigation. This review, indeed, aims to fill this gap, analyzing studies that explore digital game-based learning (DGBL) for teacher training and/or teacher attitude in using DGBL in their professional activity. We searched the following bibliographic databases: Scopus, ERIC, and Web of Science and after a screening 20 papers have been selected and included. Main results returned a clear framework of what the current literature presents as effective DGBL training for teachers and pre-service teachers and of facilitators and barriers that impact teachers' attitudes related to the use of DGBL at school.